Transient Asystole after Sugammadex Administration for Immediate Reversal of Deep Blockade while on Dexmedetomidine Infusion in a Super Obese Patient - Michal Gajewski; Sorochi Esochaghi (Case Reports in Anesthesiology)
Sugammadex is increasingly used to reverse aminosteroid neuromuscular blocking agents. Dosing is calculated based on actual body weight, even for those who are obese. We report a case where a super obese patient (BMI 58.5 kg/m2) developed asystole, following coadministration with dexmedetomidine, for rapid reversal after deep blockade. Although 16mg/kg of actual body weight is recommended for prompt reversal of deep blockade, dosing adjustments may be prudent in the obese population, especially when used in conjunction with other negative chronotropic agents.